An evaluation of integrated spatial technology framework for greenhouse gas mitigation in grain production in Western Australia - Engelbrecht, D.; Biswas, Wahidul; Ahmad, W. (Elsevier Science, 2013)
The International Panel on Climate Change (IPCC) predicts an increase of 0.2 C per decade for the nexttwo decades in global temperatures and a rise of between 1.5 and 4.5 C by the year 2100. Related to theincrease in world temperatures is the increase in Greenhouse Gases (GHGs) which are primarily made upof carbon dioxide (CO2), nitrous oxide (N2O), methane (CH4) and fluorinated gases. In 2004, the GHGsfrom agriculture contributed 14% of the overall global GHGs made up mainly of methane (CH4) andnitrous oxide (N2O) emissions. In Australia, the dominant source of CH4 and N2O emissions for the yearending June 2012 was found to be from the agricultural sector. With the recent introduction of the CleanEnergy Act 2011, the agricultural sector of Australia is expected to develop appropriate GHG mitigationstrategies to maintain and improve its competitiveness in the green commodity market. This paperproposes the use of Integrated Spatial Technologies (IST) framework by linking Life Cycle Assessment(LCA), Remote Sensing (RS) and Geographical Information Systems (GIS). The IST approach also integratesand highlights the use of Cleaner Production (CP) strategies for the formulation and application of costeffectiveGHG mitigation options for grain production in Western Australia (WA). In this study, the ISTframework was tested using data from an existing study (the baseline study) and two mitigation options.The analysis results revealed production and use of fertiliser as the “hotspot”, and for mitigation purposeswas replaced with pig manure in option 1, whereas option 2 emphasised crop rotation system/s.